Early Summer Soil Moisture Contribution to Western European Summer Warming. Issue 17 (30th August 2021) - Stegehuis, A. I.; Vogel, M. M.; Vautard, R.; Ciais, P.; Teuling, A. J.; Seneviratne, S. I.
Abstract: Warm European summer temperatures are often preceded by low soil moisture conditions, but also depend on the atmospheric circulations and associated rainfall that may trigger drought to persist and land‐atmosphere feedbacks to take place. The quantitative role of early summer soil moisture (ESSM) trends, versus that of trends in atmospheric circulations and other large‐scale drivers (LS), in explaining the long‐term trends in summer warming have not been investigated so far. Using regional climate simulations with forced large‐scale circulation and different possible initial soil moisture, we show that the increasing ESSM deficit explains almost all of the warming summer trend (1980–2011) in Western Europe (∼0.1–0.2°C . decade −1, p‐value < 0.05). It also contributed a similar amount to summer warming trend in Eastern Europe, although here LS explains a much larger part of the overall warming. Our results emphasize the crucial role of the pre‐summer water cycle in current and future regional evolutions of Western European summer climate. Plain Language Summary: During the last decades the summers in Europe have become warmer. It is important to understand this change in order to be able to mitigate future warmer summers. The warming is partly due to local and regional drying of the soil, but also to the climate and winds at a larger scale than Europe. This has already been found in other work, but the two contributions were never quantified before in the long‐term trend of summer warming. In this research we investigate how many degrees the soil moisture and the larger scale climate contributed to the European summer warming. We found that a changing soil moisture at the beginning of the summer caused a temperature increase of ∼0.1–0.2°C . decade −1 in Central and Western Europe. This was the same in Eastern Europe but there we found that the larger scale climate was more important and caused an increase of up to ∼1°C . decade −1 . This means that adapting land management policies to hold more winter and spring water can especially have a positive effect on the climate in Central and Western Europe and may be able to reduce extreme warm summers in the future. Key Points: Increasing early summer soil moisture deficit explains almost all of the rapid recent warming summer trend in Western Europe Large‐scale drivers explain up to 1°C.decade−1 of the warming summer trend in Eastern Europe Our results emphasize a crucial role of pre‐summer water cycling in current and future evolutions of Western European summer climate